Just like Martin - Davis, Ossie (New York : Simon & Schuster Books for Young Readers, 1992)
Following the deaths of two classmates in a bomb explosion at his Alabama church, fourteen-year-old Stone organizes a children's march for civil rights in the autumn of 1963.
Book Links (A.L.A.).
School Library Journal.
Wilson's Junior High School.
5.9.
5.9
5-8
Keywords: African Americans -- Fiction; Civil rights movements -- Fiction; African Americans -- Fiction; Civil rights movements -- Fiction; United States -- History -- 1961-1969 -- Fiction; United States -- History -- 1961-1974 -- Fiction